The Urgency of Religious Tolerance for Islamic Educational Institutions - Muhammad Syarif Hidayatulloh (Penerbit Hellow Pustaka, 2025)
As a nation that has a variety of diversity, Indonesia has the potential to cause conflicts among citizens, both in the smallest scope and on a large scale. The diversity of languages, cultures, tribes, and even religions is a gift that must be recognized as a form of noble heritage of our predecessors. One of the triggers for the emergence of intolerance behavior is the existence of differences in religious beliefs, an exclusive attitude in understanding religious problems in society. Islamic educational institutions have a responsibility that is not light in providing an inclusive understanding of society and teaching tolerance and noble religious values. The substance of religious teachings such as tolerance and religious harmony towards school residents should be internalized as early as possible. This paper explains the importance of religious harmony, tolerance, and for Islamic educational institutions.